2016
DOI: 10.1111/bjh.14022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ELN recommendations in the management of first‐line treated chronic myeloid leukaemia patients: a French cross‐sectional study

Abstract: The availability of tyrosine kinase inhibitors has extended therapeutic options for chronic myeloid leukaemia (CML) patients. Monitoring recommendations and clinical response goals have recently been updated. The objective of this study was to describe the profile of CML patients in chronic phase currently receiving first-line therapy, including treatment, monitoring and response kinetics. A multicentre, cross-sectional, epidemiological survey in unselected chronic phase CML patients in France attending consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Sokal risk scores observed in our study, as well as in the French epidemiological survey (Etienne et al , ), the GIMEMA trial (Castagnetti et al , ), the ENEST1st trial (Hochhaus et al , ) and a phase II Turkish trial (Saydam et al , ), are comparable, with a low Sokal score in 46·4%, 42·3%, 43·0%, 34·6% and 54·5% of patients respectively; an intermediate score in 34·4%, 39·7%, 36·0%, 37·5% and 39·3% respectively; and a high score in 14·2%, 18·1%, 21·0%, 18·1% and 6·3% respectively. However, in the ENESTnd study, patients with high Sokal risk were comparatively more represented (28·0%) (Saglio et al , ).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Sokal risk scores observed in our study, as well as in the French epidemiological survey (Etienne et al , ), the GIMEMA trial (Castagnetti et al , ), the ENEST1st trial (Hochhaus et al , ) and a phase II Turkish trial (Saydam et al , ), are comparable, with a low Sokal score in 46·4%, 42·3%, 43·0%, 34·6% and 54·5% of patients respectively; an intermediate score in 34·4%, 39·7%, 36·0%, 37·5% and 39·3% respectively; and a high score in 14·2%, 18·1%, 21·0%, 18·1% and 6·3% respectively. However, in the ENESTnd study, patients with high Sokal risk were comparatively more represented (28·0%) (Saglio et al , ).…”
Section: Discussionsupporting
confidence: 82%
“…The median age of patients in this study was 54 years, which is consistent with a recent CML‐CP French cross‐sectional epidemiological survey in first‐line TKI treated patients in which median age was 61 years with a median time since diagnosis of 4 years. In this survey, imatinib was the most prescribed TKI in current practice (81·1%), and nilotinib the second one (12·4%) with a tendency to be preferentially used in patients aged under 65 years (Etienne et al , ). As anticipated in an observational study reflecting daily clinical practice, median age was higher than the reported 47 years in the ENEST‐Newly Diagnosed patients (ENESTnd) randomized clinical trial that led to the approval of nilotinib for first‐line use (Saglio et al , ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…An observational study of 705 patients from 36 centers in France reported that MR monitoring in routine clinical practice is closely aligned with the updated recommendations. The authors of the study highlight the majority of patients were still receiving first‐line treatment and were in optimal response . There were no reported differences in monitoring patterns according to insurance status, which suggests that lower rates of monitoring were not the result of issues with insurance.…”
Section: Discussionmentioning
confidence: 99%